Accumulation of (E)-4-Hydroxy-2-nonenal and n-Hexanal, Degradation Products of Lipid Peroxides, in Mouse Lung and Liver - SANO, Mitsuaki; HAGIWARA, Makoto; FUJITA, Masahiro; YOSHINO, Kyoji; TOMITA, Isao (Biological & pharmaceutical bulletin, 1993)
Effects of lipid peroxide breakdown products, (E)-4-hydroxy-2-nonenal (4-HN) and n-hexanal, on mouse lung lesion were examined. When 4-HN was injected i.v., the plasuma level of 4-HN increased just after the injection and then decreased immediately. The amounts of 4-HN increased in the liver and lung were ca. 0.085 and 0.43% to the dose administered, respectively, 5min after the injection. Reduced glutathione (GSH) content and both GSH peroxidase (GSH-Px) and GSH reductase (GSSGR) activities in the lung were decreased significantly by 4-HN treatment. On the other hand, in the case of i.v. injection of n-hexanal into mice, the amount of n-hexanal detected in the lung was 5.0% to that of 4-HN, and no effect on the activities of GSH-Px and GSSGR and the content of GSH was observed.These results suggest that 4-HN generated from lipid peroxides would be transferred into the lung and cause the lung lesion through the inhibition of GSH-dependent antioxidative defense systems.